2020
DOI: 10.1186/s12645-020-00066-4
|View full text |Cite
|
Sign up to set email alerts
|

Algae-meditated route to cuprous oxide (Cu2O) nanoparticle: differential expression profile of MALAT1 and GAS5 LncRNAs and cytotoxic effect in human breast cancer

Abstract: Background Breast cancer (BC), as the most widely recognized disease in women worldwide, represents about 30% of all cancers impacting women. This study was aimed to synthesize Cu2O nanoparticles from the cystoseira myrica algae (CM-Cu2O NPs) assess their antimicrobial activity against pathogenic bacteria and fungi. We evaluated the expression levels of lncRNAs (MALAT1 and GAS5) and apoptosis genes (p53, p27, bax, bcl2 and caspase3), their prognostic roles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 103 publications
1
7
0
Order By: Relevance
“…It is wellknown that excessive generation of ROS/RNS, oxidative stress, and cancer cell Sub G1 arrest is connected to DNA damage and apoptosis/necrosis [41,42]. Our results agree with earlier studies that observed induction of apoptosis as a result of green synthesized nanoparticles [40,43]. Of late, endoplasmic reticulum stress-mediated induction of apopto-sis has also been reported in response to CuO NP treatment in Wistar rats [44].…”
Section: Induction Of Apoptosis In Response Of Cuo Npsupporting
confidence: 92%
See 1 more Smart Citation
“…It is wellknown that excessive generation of ROS/RNS, oxidative stress, and cancer cell Sub G1 arrest is connected to DNA damage and apoptosis/necrosis [41,42]. Our results agree with earlier studies that observed induction of apoptosis as a result of green synthesized nanoparticles [40,43]. Of late, endoplasmic reticulum stress-mediated induction of apopto-sis has also been reported in response to CuO NP treatment in Wistar rats [44].…”
Section: Induction Of Apoptosis In Response Of Cuo Npsupporting
confidence: 92%
“…Apoptosis is considered a significant anticancer mechanism that involves the activation of a sequence of molecular events culminating into cell death with cellular, 3 Journal of Nanomaterials morphological, and biochemical changes [40]. It is wellknown that excessive generation of ROS/RNS, oxidative stress, and cancer cell Sub G1 arrest is connected to DNA damage and apoptosis/necrosis [41,42].…”
Section: Induction Of Apoptosis In Response Of Cuo Npmentioning
confidence: 99%
“…An in vitro study indicated that CuONPs treatment increased the expression of the P53 tumor suppressor gene, and an elevation in the BAX / BCL2 ratio revealed that a mitochondria-mediated mechanism is engaged in CuONPs-induced programmed cell death 17 . The findings of another investigation showed that the expression levels of P21 , BAX , and CASP3 were considerably elevated, and BCL2 dramatically declined in CuONPs-treated SKBR3 cells as compared to normal cells 83 .…”
Section: Resultsmentioning
confidence: 95%
“…Nanogels represent a versatile platform for drug delivery, with tunable properties. Clinical trials are necessary to assess their safety and effectiveness in different therapeutic contexts [ 162 , 163 ]. Cationic liposomes and chitosan nanoparticles offer unique advantages for gene and nucleic acid delivery.…”
Section: Cancer Therapy Using Nanomaterialsmentioning
confidence: 99%